The broken eye (Lightbringer, 3,, 2014)
Without the protection of Gavin Guile, who has been captured and enslaved and has lost his powers, Kip, Teia, and Karris fight to survive a secret war between the nobles, rebels, and an ancient order of stealthy assassins called The Broken Eye.

The blood mirror (Lightbringer, 4,, 2016)
"The Seven Satrapies have collapsed into four-and those are falling before the White King's armies. Gavin Guile, ex-emperor, ex-Prism, ex-galley slave, formerly the one man who might have averted war, is now lost, broken, and trapped in a prison crafted by his own hands to hold a great magical genius. But Gavin has no magic at all. Worse, in this prison, Gavin may not be alone. Kip Guile will make a last, desperate attempt to stop the White King's growing horde. Karris White attempts to knit together an empire falling apart, helped only by her murderous and possibly treasonous father-in-law Andross Guile. Meanwhile, Teia's new talents will find a darker use-and the cost might be too much to bear. Together, they will fight to prevent a tainted empire frombecoming something even worse"--